Materials Processing Fundamentals 2017 - Allanore, Antoine; Lambotte, Guillaume; Lee, Jonghyun; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Covering the physical and numerical modeling of materials processing, this book includes contributions across the range of metals and minerals. This collection offers a unique opportunity to present models and results for key processes involved in extraction, joining, separation, and casting of materials. The corresponding fundamentals of mass and heat transport as well as physical and thermodynamics properties are addressed, allowing for a cross-disciplinary vision of the field.
Part 1: Steelmaking -- Development of ultrahigh-basicity mold fluxes for peritectic steel continuous casting -- Part 2: Metal Extraction -- Applied statistical analysis on the calcination process in the ferronickel production -- The Chemical Stability and Electrochemical Behavior of Dy2O3 in Molten CaCl2 -- Part 3: Molten & Gas State Processing -- Influence of Oxygen on Surface Tension of Zr -- Part 4: Solid-State Processing -- Evaluation feature of Nano Grain Growth of TiO2 Thin Film via Sol- gel Route -- Part 5: Molten & Gas State Processing -- Thermal analyses of silver-based sulfosalts in air -- Oscillation of a Zirconium Droplet - Experiments and Numerical Simulations -- Gallium Evaporation Behavior for Purification in Molecular Beam Epitaxy (MBE) -- Mass Transfer of Al and Ca Between Silicon and Synthetic SiO2-CaO-Al2O3 Slags -- Part 6: Poster Session -- The interface characteristics of high-temperature melt of CaO-Al2O3-MgO-SiO2 system -- Effect of Modeling flows on Mixing Time in 40t Ladle with Bottom Gas Blowing Process -- Study Of Electrochemical Reactor Filter-Press Used In The Treatment Of Industrial Waste By COMSOL -- Genetic Influence of Mold Corner Structure on the Strand Corner Temperature in Secondary Cooling Zone during Slab Continuous Casting.
Keywords: Materials -- Analysis; Materials; Metals; Characterization and Analytical Technique; Materials Engineering; Metals and Alloys